Ethnobotanical study on wild edible plants traditionally used by Messiwa people, Morocco - Ridwane Ghanimi; Ahmed Ouhammou; Abdellah Ahouach; Mohamed Cherkaoui (BMC, 2022)
Abstract Background The traditional knowledge on wild edible plants has been shown in many studies a worrying decline throughout the last few decades. Therefore, the first aim of this study was to document the population knowledge on wild edible plants among the Messiwa people. The second objective was to assess the traditional knowledge of our informants according to their socio-economic status. Methods The survey was conducted among 149 informants through a semi-structured questionnaire. The relative importance of the plants was obtained by calculating the relative frequency of citation (RFC) for each species. To compare means, we used Student's t test for two-group comparisons and Snedecor's F-test for multi-group comparisons. The multi-range Duncan test was used for multiple mean comparisons. The correspondence factor analysis (CFA) was also used. Results A set of 64 species belonging to 56 genera from 34 families has been collected and identified. The species used for nutritional and medicinal purposes represent 56%, while 44% were used exclusively as nutritional plants. The most used parts are, respectively, the aerial parts (58%), the fruits (17%), the underground parts (13%), the seeds (8%), and finally the flowers (5%). On the other hand, the higher level of knowledge on wild edible plants was found among women, the elderly, illiterate, married people, and those engaged in agricultural occupations. Conclusion This work could be a basis to be reproduced on other regions in Morocco and to be widened through pharmacological and nutritional studies in order to promote and valorize these wild edible plants.